Long-Term Effectiveness of Brodalumab for the Treatment of Moderate-To-Severe Psoriasis: A Real-Life Multicenter Study of Up to 3 Years in a Real-Life Italian Cohort - Giacomo Caldarola; Marco Galluzzo; Nicoletta Bernardini; Elisabetta Botti; Eleonora De Luca; Clara De Simone; Marco Mariani; Gaia Moretta; Sabatino Pallotta; Elena Campione; Ketty Peris (Mattioli1885, 2024)
Introduction: Data about the long-term effectiveness of brodalumab could be valuable in assessing patient adherence to treatment and improving psoriasis management. Objective: The aim of our study was to evaluate the drug survival of brodalumab and identify any predictive factors for discontinuation. Methods: A multicenter retrospective study was conducted in patients with moderate-to-severe psoriasis who were treated for up to 3 years. We extracted data from patient files, related to the characteristics of the patients and the disease. Drug survival analysis was descriptively analyzed using Kaplan-Meier survival curves. Univariable and multivariable analyses were performed to assess baseline patient characteristics that predicted clinical response. Results: The study included 90 patients. Among them, 28 (31.1%) suspended brodalumab through the observation period. At weeks 52, 104 and 156 the median PASI score were 0.0 [0.0 - 0.8], 0.0 [0.0 - 1.0] and 0.0 [0.0 - 0.0], respectively.  The estimated cumulative survival rates at weeks 52 and 104 were 86.32% and 78.09%, respectively. In the multivariable survival analysis, predictor factors for overall discontinuation included body mass index (BMI) (OR 1.10, 95% CI 1.03 - 1.18), baseline PASI (OR 1.06, 95% CI 1.02 - 1.10), and psoriatic arthritis (OR 5.05, 95% CI 0.89 - 13.50). Conclusions: Brodalumab has shown long-term effectiveness for up to 3 years. Considering baseline disease severity and patient characteristics could aid in optimizing the long-term management of psoriasis.